Psychometric Testing of the European Organisation for Research and Treatment of Cancer Quality of Life Questionnaire–Chemotherapy-Induced Peripheral Neuropathy 20-Item Scale Using Pooled Chemotherapy-Induced Peripheral Neuropathy Outcome Measures Standardization and Alliance for Clinical Trials in Oncology A151408 Study Data. Issue 3 (May 2019) - Smith, Ellen M. Lavoie; Banerjee, Tanima; Yang, James J.; Bridges, Celia M.; Alberti, Paola; Sloan, Jeff A.; Loprinzi, Charles
Abstract : Background: No criterion-standard patient-reported outcome measure of chemotherapy-induced peripheral neuropathy (CIPN) exists. Objectives: The aims of this study were to reevaluate the sensitivity, reliability, and validity of the European Organisation for Research and Treatment of Cancer Quality of Life Questionnaire–CIPN (QLQ-CIPN20) measure and suggest possible revisions that could strengthen it. Methods: Cross-sectional QLQ-CIPN20 data from 8 European countries (n = 271) were pooled with data from 4 North American multisite CIPN intervention trials (n = 884). The combined sample (N = 1155) included patients with varied cancer diagnoses who had received neurotoxic chemotherapy. Item score ranges, Cronbach's α, and exploratory factor analysis were used to evaluate sensitivity, internal consistency, and structural validity. Results: Individual item mean scores ranged from 1.21 to 2.34 ( SD range, 0.55–1.17). All item scores encompassed the entire 1 to 4 range. We recommend that 4 items be removed because of low item-item score correlations ( r < 0.30). On the basis of the remaining 16 items, 88% of the variance was explained by 2 factors whose Cronbach's α coefficients were .90 and .85. However, items lacked conceptual alignment with previously published factor structures. Conclusion: Using a large, diverse sample of European and North American participants, the reduced 16-item QLQ-CIPN20 is sensitive and internally consistent. However, factor analysis results revealed an unstable factor structure. Implications for Practice: The use of a reliable, valid, and sensitive criterion-standard QLQ-CIPN20 variant in clinical practice settings could improve function, quality of life, and CIPN symptom control by facilitating patient reporting and thereby clinician awareness of this underrecognized consequence of cancer therapy.